Real-world multicentre experience of first-line afatinib in patients with EGFR-mutant advanced non-small cell lung cancer - Liam, Chong Kin; Chai, Chee Shee; Ho, Gwo Fuang; Alip, Adlinda; Abdul Wahid, Mohd Ibrahim; Abdullah, Matin Melor; Foo, Yoke Ching; How, Soon Hin; Zaatar, Adel; Lam, Kai Seng; Leong, Kin Wah; Seng Hoi, John Low; et al. (2019)
Background : Afatinib is an irreversible, second-generation epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKI) that has been shown to be more potent than platinum doublet chemotherapy as well as the firstgeneration EGFR-TKI in patients with EGFR-mutant advanced non-small cell lung cancer (NSCLC). This study aimed to evaluate the efficacy, side-effects and resistance mechanisms of first-line afatinib in a real-world setting. Method : This is a multicentre observational study of Malaysian patients with EGFR-mutant advanced NSCLC started on first-line afatinib from 1st October 2014 to 30th April 2018. Results : The demographic and clinical characteristics of 85 patients who met the study criteria are shown in Table 1. EGFR mutations harboured by the tumours included exon 19 deletion in 80.0%, exon 21 L858R point mutation in 12.9%, and rare or complex EGFR mutations in 7.1%. Of the patients. 18.8% of the patients had an ECOG performance status of 2-4, 29.4% had baseline symptomatic brain metastases and 17.6% had abnormal organ function. Table 2 shows the starting dose, dose adjustment and optimal dose of afatinib. Afatinib 40 mg or 30 mg once daily were the most common starting and maintenance doses. Treatment outcome (Tables 3, 4 and 5; Figures 1 and 2) Response to afatinib The objective response rate (ORR) was 76.5% while the disease control rate (DCR) was 95.3% on first-line afatinib (Table 3). Two (2.4%) patients had complete response. Patients without baseline brain metastases had a significantly higher ORR than those with baseline brain metastases (Table 4). There was a trend for patients in whom the dose of afatinib was reduced to experience higher ORR than those without dose adjustment. On multivariate subgroup analyses involving covariates shown in Table 4, patients without symptomatic brain metastases had significantly higher ORR than that of those with symptomatic brain metastases (81.7% versus 56.0%; OR, 4.51; 95% CI, 1.45–14.00; p = 0.009); while patients with afatinib dose reduction had significantly higher ORR than that of those without dose adjustment (88.5% versus 65.3%; OR, 5.53; 95% CI, 1.32–23.24; p = 0.019). Progression-free survival 56 (65.9%) patients had PD at the time of analysis with a mPFS of 14.2 (95% CI, 11.85 – 16.55) months (Figure 1) Conclusion : Afatinib is an effective first-line treatment for patients with EGFR-mutant advanced NSCLC with good response and disease control rates as well as long PFS even in patients with unfavourable clinical characteristics. The side-effects of afatinib were manageable and acquired T790M mutation was the acquired resistance mechanism in 42% of patients with PD who underwent rebiopsy